Verification and analysis of advanced tuneable nonlinear vibration energy harvester. (15th April 2023) - Sosna, Petr; Rubeš, Ondřej; Hadaš, Zdenek
Graphical abstract: Highlights: Multidisciplinary model of coupled magneto-piezo-elastic system is developed. Combined exponential-Duffing magnetic nonlinearity fits well with experimental results. Design configurations of the piezoelectric energy harvester were analysed for harvesting of maximal power. Presented results could be used for design of self-adapting energy harvesting system. Abstract: This paper deals with advanced techniques of transducing kinetic energy of vibration into useful electricity. Piezoelectricity is widely used as one of the conversion principles and nonlinearities are studied. Motivated by possible applications in aircraft or railways, we seek to find the best system configuration for various forcing conditions to maximize the power generation for more advanced wireless sensing stations. The results for vibration amplitude 0.5 g indicate that monostable regime is suitable for tuning for frequencies lower than the natural frequency of the linear resonator. The best type of oscillation for bistable regime is always in-well single-periodic behavior and is suitable for tuning in the entire frequency range from 20 to 65 Hz. The results show the versatility of this simple energy harvester and could serve as theoretical background for a new tunable energy harvester that will be able to adapt to changes in excitation. This design could also be used in smart sensing structures.